Soil-transmitted helminth infections in Nigerian children aged 0–25 months - Kirwan, P.; Asaolu, S.O.; Abiona, T.C.; Jackson, A.L; Smith, H.V.; Holland, C.V. (Cambridge University Press, 2020)
Cambridge University Press, p.1-6